Role of vacancy defects in Al doped ZnO thin films for optoelectronic devices. (7th November 2017) - Rotella, H; Mazel, Y; Brochen, S; Valla, A; Pautrat, A; Licitra, C; Rochat, N; Sabbione, C; Rodriguez, G; Nolot, E
Abstract: We report on the electrical, optical and photoluminescence properties of industry-ready Al doped ZnO thin films grown by physical vapor deposition, and their evolution after annealing under vacuum. Doping ZnO with Al atoms increases the carrier density but also favors the formation of Zn vacancies, thereby inducing a saturation of the conductivity mechanism at high aluminum content. The electrical and optical properties of these thin layered materials are both improved by annealing process which creates oxygen vacancies that releases charge carriers thus improving the conductivity. This study underlines the effect of the formation of extrinsic and intrinsic defects in Al doped ZnO compound during the fabrication process. The quality and the optoelectronic response of the produced films are increased (up to 1.52 m Ω ⋅ c m and 3.73 eV) and consistent with the industrial device requirements.